A study of adolescents’ academic achievement in relation to their personality traits and age (International Journal of Food and Nutritional Sciences, 2022)
This study intended to test the proposition that there is a relationship between teenage academic success and personality traits. Furthermore, the study aimed to assess the influence of teens' age on their academic achievement. Two hundred young individuals from the Darbhanga district of Bihar, India, who were engaged in academic programs at the intermediate to post- graduate levels made up the sample. Purposive-cum-incidental sampling is a sample approach that was used to choose the participants. The individuals' academic achievement was ascertained by the researchers by adding up all of the grades they had earned throughout the preceding three years.